C.selected poster presentations: quality nursing care: patient's perspectives and the nursing response (preliminary report) - Papadopoulos, Irena Rena; Beadmoore, A.; Charalambous, Andreas (My University, 2006)
Introduction: Cancer remains a major cause of morbidity and mortality within Cyprus affecting one in four of the population. Alongside the nature of cancer has changed dramatically in recent years, including shorter inpatients stays, an increasing older cancer population and significant improvements in treatments outcomes and effectiveness. Despite the recent changes to service delivery, little attention in terms of the quality of health services has yet been focused on cancer patients and nurses. In light of these factors, the need to focus the exploration of the experience on those involved in the delivery and receipt of the care and its’ potential value to nursing practice within the cancer care setting is important. Cancer patients are better informed than before and have increasing expectations from the health care system. The pressures of this most educated, consumer-oriented generation will soon be felt in health care as they age and also begin to manage care on behalf of their parents.
Keywords: Cancer; Patients; Nursing